Sepsis affects kidney graft function and one-year mortality of the recipients in contrast with systemic inflammatory response - Protus, Marek; Uchytilova, Eva; Indrova, Veronika; Lelito, Jan; Viklicky, Ondrej; Hruba, Petra; Kieslichova, Eva (Frontiers in Medicine, 2022)
Background Infections remain a major cause of morbidity and mortality after kidney transplantation. The aim of our study was to determine the effect of sepsis on kidney graft function and recipient mortality. Methods A prospective, observational, single-center study was performed. Selected clinical and biochemical parameters were recorded and compared between an experimental group (with sepsis, n = 34) and a control group (with systemic inflammatory response syndrome, n = 31) comprising kidney allograft recipients. Results Sepsis worsened both patient (HR = 14.77, p = 0.007) and graft survival (HR = 15.07, p = 0.007). Overall one-year mortality was associated with age (HR = 1.08, p = 0.048), APACHE II score (HR = 1.13, p = 0.035), and combination immunosuppression therapy (HR = 0.1, p = 0.006), while graft survival was associated with APACHE II (HR = 1.25, p = 0.004) and immunosuppression. In sepsis patients, mortality correlated with the maximal dose of noradrenalin (HR = 100.96, p = 0.008), fungal infection (HR = 5.64, p = 0.024), SAPS II score (HR = 1.06, p = 0.033), and mechanical ventilation (HR = 5.97, p = 0.033), while graft survival was influenced by renal replacement therapy (HR = 21.16, p = 0.005), APACHE II (HR = 1.19, p = 0.035), and duration of mechanical ventilation (HR = 1.01, p = 0.015). Conclusion In contrast with systemic inflammatory response syndrome, septic kidney allograft injury is associated with early graft loss and may represent a significant risk of mortality.